PENGARUH RETURN ON ASSETS, LEVERAGE, CORPORATE GOVERNANCE, DAN KARAKTER EKSEKUTIF TERHADAP TAX AVOIDANCE (Students' Journal of Accounting and Banking, 2015)
This research aimed to exam the impact of financial statement indicator to tax avoidance. ROA, leverage, corporate governance, and the executive character were used as an independent variable which were assumed have an impact to tax avoidance (dependent variable) proxied by Cash Effective Tax Rates (CETR). This research do on registered company in Corporate Governace Perception Index (CGPI) on 2011 – 2013 period with 60 observation data for 3 years and the elected company become a sample on this observation its 37 company. The sample collection techniques conducted of purposive sampling. Analysis of the data used is double linear regression analysis test. Tax evasion it’s the way for saving the tax action when still in the corridor of the law. Result of this observation showing if that variable ROA its take a positive effect its not significant to tax avoidance, leverage witch the negative effect to significant tax avoidance, Corporate Governance have a negative effect to tax avoidance and the executive negative character react its not significant to tax avoidance. Advice for researchers next to add of other variables that not yet used and the variable is having contribution in affecting tax avoidance.Keywords: Tax Avoidance, Return On Assets, Leverage, Corporate Governace and Executive Character